Development of Pop Up Book Learning Media on the Material of the Form of Matter and its Changes Based on Problem Based Learning to Improve the Learning Outcomes of Science for Grade IV Elementary School - Hanif Thalia Regina; Desi Wulandari (Postgraduate, University of Mataram, 2025)
The lack of maximum use of learning media is due to the limited ability of teachers to create creative and innovative media, as well as the delivery of material only by lecturing, especially in class IV IPAS subject matter on the form of substances and their changes makes students quickly feel bored, so that student learning outcomes are low. This study aims to develop products, test the feasibility, and effectiveness of pop up book media based on problem-based learning (PBL) learning models. This type of research, Reserch and Development (R&D) Borg and Gall model with the subject of 22 fourth grade students of SDN Ngaliyan 01. Data collection techniques through observation, interviews, questionnaires and tests. The results of media validation received 91.66% by material experts and 92.61% by media experts with a very feasible category. The N-Gain test result was 0.71 in the high category. Referring to these results, there was an increase in the average student learning outcomes from the pre-test score of 56.18 to 86.72 in the post-test after using Pop Up media based on problem-based learning (PBL), so Pop Up Book is said to be feasible and effective in improving student learning outcomes.